Forbedring av rutiner rundt pasienter med vagusnervestimulator - Tørris, Christine; Schøyen, Kari Helen; Wiklund, Elin Merete (Nordisk tidsskrift for helseforskning, 2015)
Improving routines for patients with vagus nerve stimulation Background: Vagus Nerve Stimulator (VNS) is a form of therapy which may reduce the frequency of seizures in people with epilepsy, who do not achieve remission with antiepileptic drugs. A corresponding magnet providing an additional dose of stimulation may stop or shorten the intensity of the seizure. Objective Investigate the practice and procedure regarding use and storage of a VNS Therapy magnet, to see whether introduction of a new routine with a permanent seat for VNS magnet may contribute to increased availability of the magnet. Method Registration of the magnets location was performed before, and after the magnetic board intervention. In addition staff answered a questionnaire related to experiences around storage of magnet. Results The number of not located magnets dropped from 70% to 25 % after the intervention. Conclusion A magnetic board as a storage area for VNS magnet on the patient’s room increases the availability of the magnet.